2005
DOI: 10.1038/sj.npp.1300952
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive Steroids are Altered in Schizophrenia and Bipolar Disorder: Relevance to Pathophysiology and Therapeutics

Abstract: Evidence suggests that neuroactive steroids may be candidate modulators of schizophrenia pathophysiology and therapeutics. We therefore investigated neuroactive steroid levels in post-mortem brain tissue from subjects with schizophrenia, bipolar disorder, nonpsychotic depression, and control subjects to determine if neuroactive steroids are altered in these disorders. Posterior cingulate and parietal cortex tissue from the Stanley Foundation Neuropathology Consortium collection was analyzed for neuroactive ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 157 publications
2
125
0
1
Order By: Relevance
“…Notably, allopregnanolone has been shown to reduce alcohol withdrawal symptoms in voluntary and chronic alcohol-drinking rats (Martin-García et al 2007) as well as reduce prenatal stress (Zimmerberg and Blaskey 1998) and cocaine-induced kindling in mice (Leskiewicz et al 2003). In humans, high levels of both progesterone and allopregnanolone have been observed in schizophrenia (Marx et al 2006) anxiety and panic disorders (Brambilla et al 2003(Brambilla et al , 2005 as well as after laboratory manipulated panic (Eser et al 2005). It may be the case then, that increased levels of progesterone in early abstinent CD females potentially represent a compensatory adaptation to an enhanced distressed state, characterized in the current sample, by increased levels of cortisol and enhanced negative mood.…”
Section: Discussionmentioning
confidence: 65%
“…Notably, allopregnanolone has been shown to reduce alcohol withdrawal symptoms in voluntary and chronic alcohol-drinking rats (Martin-García et al 2007) as well as reduce prenatal stress (Zimmerberg and Blaskey 1998) and cocaine-induced kindling in mice (Leskiewicz et al 2003). In humans, high levels of both progesterone and allopregnanolone have been observed in schizophrenia (Marx et al 2006) anxiety and panic disorders (Brambilla et al 2003(Brambilla et al , 2005 as well as after laboratory manipulated panic (Eser et al 2005). It may be the case then, that increased levels of progesterone in early abstinent CD females potentially represent a compensatory adaptation to an enhanced distressed state, characterized in the current sample, by increased levels of cortisol and enhanced negative mood.…”
Section: Discussionmentioning
confidence: 65%
“…Both 3a,5a-THP and 3a,5a-THDOC enhance neuronal inhibition at binding sites on GABA A receptors (Hosie et al, 2006) and produce behavioral effects similar to those of ethanol. These GABAergic steroids are potent positive modulators of GABA A receptors, producing pharmacological effects in nanomolar concentrations (Morrow et al, 1987), and studies suggest that modulating GABAergic steroid levels may have therapeutic value for treating multiple psychiatric disorders (Marx et al, 2006;Morrow, 2007;Rasmusson et al, 2006;Strohle et al, 2002;Uzunova et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that alterations in cortisol and DHEA-S levels may play a role in the pathophysiology of schizophrenia [3,16,[20][21][22][23]. Serum cortisol and DHEA-S levels may be used as a biological marker for the diagnosis of schizophrenia; however, further studies with larger sample sizes are warranted to support this finding [3].…”
Section: Introductionmentioning
confidence: 94%